Determination of heavy metals in air particulate matter by using ion chromatography - Rahmalan, Ahamad; Abdullah, M. Zahari; Sanagi, M. Marsin; Rashid, M. (Elsevier, 1996)
In recent years, ion chromatography has been increasingly used for the separation and determination of heavy metals. In this study, the separation of Cu2+, Ni2+, Zn2+, Co2+, Pb2+ and Fe2+ in airborne particulate samples was achieved by the use a complexing eluent containing 20 mM oxalic acid and 20 mM citric acid adjusted to pH 3.6 with lithium hydroxide. Upon elution, the separated metal ions were reacted with 4-(2-pyridylazo)resorcinol to form coloured complexes in a postcolumn reactor and detected by using a UV-Vis detector at 520 nm. The calibration graphs for the metal ions were linear in the range 1.0–3.0 μg/ml for Cu2+, Ni2+, Co2+ and Zn2+, 8.0–24.0 μg/ml for Pb2+ and 2.0–6.0 μg/ml for Fe2+. Detection limits for a 25-μl sample solution were 2.2, 0.9, 6.6, 0.9, 1.8 and 2.1 μg/l for Cu2+, Ni2+, Zn2+, Co2+, Pb2+ and Fe2+, respectively. The technique was optimized and validated by analysing the NIST standard reference materials SRM 1648 Urban Particulate Matter and SRM 1633b Coal Fly Ash.